(untitled) (Bangladesh Journal of Nuclear Medicine, 2024)
Mesenteric cysts are rare intra-abdominal lesions, and they have a wide range of clinical signs and symptoms that make pre-operative diagnosis difficult. Diagnosis is often incidental. Although the exact cause of mesenteric cysts is unknown, obstruction of the lymphatic system due to trauma, infection, or tumors is thought to play a role. The optimal treatment is surgical excision of the cyst with laparotomy or laparoscopy. We report a case of a 65-year-old female with ovarian cancer who had an incidental finding of a mesenteric cyst during an 18F FDG PET-CT scan. Bangladesh J. Nuclear Med. 27(1): 127-129, 2024